PENENTUAN BOBOT PERNYATAAN KESEHATAN PESERTA ASURANSI JIWA PEMBIAYAAN SYARIAH MENGGUNAKAN ALGORITMA BACKPROPAGATION (Studi Kasus Asyki Microtakaful) - Hosein, Puspa Eosina; Irawan, Ujang; Kusumah, Fitrah Satrya Fajar (Fakultas Teknik dan Sains, Universitas Ibn Khaldun Bogor, 2017)
Asyki Microtakaful (AM) has 5 statements of healthy, all of that healthy statements become a determinant for next process of policy is participant non-medical is potential or no. The process express of potential participant or no are do while underwriting. In the fifth process healthy statement is assessed based on right condition or no. For getting fix assessment then need the weight from all of that statement. The aim from this research is to get the weight from each participant's healthy statement with use closely algorithm back propagation. This research has made new weight from healthy statement, the weight already has compatible with the accuration by the condition healthy statement is ready. The result that we got for network architecture's pattern 5-5-1 (5 input, 5 hidden layer and 1 output) has error's assessment smaller than architecture's pattern 5-3-1 and 5-2-1 with epoch's score maximum 86 then score of mean error (ME) 0.038, mean squared error (MSE) 0.019 and mean absolute percentage error (MAPE) 24.619, input X to Z have the average X1 = -2.27, X2 = 0.32, X3 = - 2.44, X4 = -1.36 and X5 = 0.84 from 35 data.